Environment protection in oil and gas exploration and production activities, offshore Vietnam - Bui , Hong Diem; Do , Thi Thu Phuong; Tran , Phi Hung (Petrovietnam Journal, 2022)
Oil and gas exploration and production activities in Vietnam have contributed greatly to the economic development of the country. Besides, those activities also generate waste sources that affect the environment. Thanks to the synchronous implementation of pollution management and treatment solutions, so far the offshore Vietnam oil and gas exploration and production activities have not caused any significant adverse impact on the water environment, the sediment environment, the benthic community, and the air environment. The article introduces waste sources and types of waste from offshore oil and gas exploration and production, and assesses the environmental control results in offshore Vietnam oil and gas exploration and production activities. On that basis, the paper also points out the obstacles in the process of implementing the Law on Environmental Protection [1], Decree No. 08/2022/ND-CP dated January 10, 2022 [2] for oil and gas activities.